Improving sleep quality by the mean of a smart bed - Hasan, Ferman; Qader, Mahdi A. (Technium Social Sciences Journal, 2022)
Sufficient sleep and quality sleep considered as one of the most important human needs. Less sleep may make human nerves, anxiety and less concentrate. Therefor, this paper focuses on the sleep types, and a kind of sleep bed, in order to find out how such a bed improve quality of sleep, and how a specific game helps to make a child improve their quality sleep? Also, this paper focuses on some environment factors may have effect on the sleep quality such as temperature, mattress softness, luminosity, air pressure and humidity. For this purpose, this research relays on the two experiments, the first one would be preparing the room with such a bed and supplies the room with measurement tools such as pressure sensors, body thermometers in order to measure sleep quality and it takes 28 days. Also, conducting a Questionnaire. The second experiment would be comparing quality sleep between standard bed and Smart bed.